PROTECTION OF CREDITORS IN THE EXECUTION FIDUCIARY GUARANTEE KENDARAAN MOTOR CREDIT - Nurwati SH., MH. (JURNAL HUKUM DE'RECHTSSTAAT, 2015)
ABSTRACTFiduciary security is legal security over on moving objects both tangible and intangible, and building or a house on the land belong to someone else, either registered or not, which cannot be burdened with mortgage rights that keep in control of the fiduciary as collateral of debt repayment. If debtor as Fiduciary giver to be insolvent, so the creditor is entitled to have the fiduciary mentioned. For repayment of the debtor and the creditor in this case is called the right separatists.  There are many direct execution in banking practice about the object credit that are not perfect bound of guarantees or not through the insurance agency. Execution is doing by creditors, which debtor accompanied or not, or the object credit guarantees owner. Execution is done by regular sales or through creditor takeover.  Protection of creditors interest doing by giving legal aspects of registration precedes rights while providing executorial title for the fiduciary receivers benefit, on the other hand, the registration arrangements for certain objects that are not listed cause haziness opportunities of law implementation if it isnot done by carefully and clearly. To protect creditors interests, at the time of the debtor defaults, so that creditors as apreferential rights receiver in debt collection and as legal evidence, so warehouse receipts guarantee that the debtor should be given the imposition of bail.Key: Execution, Fiduciary, Creditors, Debtors